Analisis Pembelajaran Daring Biologi Di Masa Pandemi Covid-19 Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Palembang: (Analysis of Biology Online Learning During the Covid-19 Pandemic Biology Study Program FKIP University of Muhammadiyah Palembang) - Desti Tria Putri; Sri Wardhani; Indawan Indawan (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
The online learning system is one from of realizing Revolution 4.0 which focuses on technology based learning. Online learning is learning without face to face directly between lecturers and students, but is carried out by utilizing information technology. The purpose of this study was to find out the description of online biology learning during the Covid-19 pandemic FKIP Muhammadiyah University of Palembang. This type of research is a qualitative research. The results of this study are that there are three activities, namely planning, implementation, and evaluation of learning. In planning activities, the lecturer make RPS or SAP and also prepares teaching materials. Besides that, students also do planning starting from the place, completeness of stationery, and readiness to learn. In the implementation of learning applications that are often used zoom and whatsapp. The learning method used is question and answer discussion. The obstacle that is very often encountered in online learning is the signal problem. The readiness of students and lecturers during the online learning process is quite good. The characteristics of students in online learning look more creative. The form of evaluation is in the form of assignments after the end of the lecture and the application used by Whatsapp. For the final semester exam, it is done in writing with the lecturer sending questions in the whatsapp group. Abstrak. Sistem pembelajaran daring salah satu bentuk untuk mewujudkan Revolusi Industri 4.0 yang menitikberatkan pembelajaran berbasis teknologi. Pembelajaran daring merupakan pembelajaran tanpa tatap muka secara langsung antara dosen dan mahasiwa, tetapi dilakukan dengan memanfaatkan teknologi informasi. Tujuan penelitian ini adalah untuk mengetahui gambaran pembelajaran daring biologi di masa pandemi Covid-19 FKIP Universitas Muhammadiyah Palembang. Jenis penelitian ini merupakan penelitian kualitatif. Hasil penelitian ini adalah terdapat tiga kegiatan yaitu perencanaan, pelaksanaan, dan evaluasi pembelajaran. Pada kegiatan perencanaan dosen membuat RPS atau SAP dan juga mempersiapkan bahan ajar selain itu mahasiswa juga melakukan perencanaan mulai dari tempat, kelengkapan alat tulis, dan kesipan belajar. Pada pelaksanaan pembelajaran aplikasi yang sering digunakan zoom dan whatsapp. Metode pembelajaran yang dipakai diskusi tanya jawab. Kendala yang sangat sering ditemui dalam pembelajaran daring adalah masalah sinyal. Untuk kesiapan mahasiswa dan dosen selama proses pembelajaran daring cukup baik. Karakteristik mahasiswa dalam pembelajaran daring ini terlihat lebih kreatif. Bentuk evaluasi berupa tugas-tugas setelah akhir perkuliahan dan aplikasi yang digunakan whatsapp. Untuk ujian akhir semester dilakukan secara tertulis dengan dosen mengirimkan soal-soal di grup whatsapp.